REGISTRATION OF SURFACE ACOUSTIC WAVES in Z-SECTIONS of PIEZOELECTRIC SINGLE CRYSTALS ZnO and CdS - I. V. Linchevsky; M. V. Chursanova (Radio Physics and Radio Astronomy, 2025)
Subject and Purpose. The subjects of this research are the internal electric field and the electric polarization vector, both existing in the volume of a deformed piezoelectric crystal. The work has been aimed at determining the dynamic electric polarization within the Z-section of a class 6 mm piezoelectric single crystal, deformed by surface acoustic waves (SAW), and estimating the sensitivity of the electrode pair of the inter-digit transducer in the mode of recording surface acoustic waves in Z-sections of the piezoelectric crystals.